2010
DOI: 10.1677/erc-10-0097
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus as a new potential antiproliferative agent in aggressive human bronchial carcinoids

Abstract: Bronchial carcinoids (BCs) are rare tumors originating from endocrine cells dispersed in the respiratory epithelium. It has been previously demonstrated that everolimus, or RAD001, an mTOR inhibitor, has potent antiproliferative effects in human endocrine tumors. Our aim was to evaluate the possible antiproliferative effects of everolimus in human BCs in primary culture. We collected 24 BCs that were dispersed in primary cultures, treated without or with 1 nM-1 mM everolimus, 10 nM SOM230 (pasireotide, a somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…In particular, the treatment of lung carcinoid cells with inhibitors of the PI3K/ AKT/mTOR pathway significantly reduced cellular growth and neuroendocrine marker expression in vitro (18,19). In Table III.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, the treatment of lung carcinoid cells with inhibitors of the PI3K/ AKT/mTOR pathway significantly reduced cellular growth and neuroendocrine marker expression in vitro (18,19). In Table III.…”
Section: Discussionmentioning
confidence: 98%
“…The AKT/mTOR signaling pathway is aberrantly activated in many tumor types (13,14,16,17). In particular, this pathway seems to play a role in tumor cell growth and proliferation in human pulmonary carcinoid cells (18,19), as well in small-cell lung cancer cells (12,20). Because of these functions, mTOR has been considered an attractive target for anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…28 In 2010, Zatelli et al observed an anti-proliferative effect of everolimus in human BC tumour cells associated with a reduction in chromogranin A level, VEGF secretion and cell viability, probably mediated by a mechanism involving IGF1 signalling. 29 mTOR expression levels together with aggressive clinical features (i.e. AC, larger tumour size, higher number of mitoses) were found to be associated with an enhanced sensitivity to everolimus.…”
Section: Preclinical Studies Of Mtor Inhibitors In Bronchial Carcinoimentioning
confidence: 89%
“…In addition, a recent preclinical study of the impact of the mTOR inhibitor, everolimus, found that it suppressed the viability of typical and atypical carcinoid lung cells in culture [20]. Thus, there is a theoretical rationale for the use of both Tyrosine-kinase inhibitor (TKIs) and mTOR inhibitors.…”
Section: Management Of Advanced/metastatic Diseasementioning
confidence: 99%